Controlled production of polysaccharides–exploiting nutrient supply for levan and heteropolysaccharide formation in Paenibacillus sp. (5th September 2016) - Rütering, Marius; Schmid, Jochen; Rühmann, Broder; Schilling, Martin; Sieber, Volker
Highlights: High throughput assisted isolation of the EPS producer Paenibacillus sp. 2H2. Characterization of EPS biosynthesis in 30 L scale. C and N source controlled production of levan, a heteropolysaccharide, or both. Analytical and rheological characterization of produced EPS. Abstract: Bacterial exopolysaccharides (EPSs) are promising sustainable alternatives to synthetic polymers. Here we describe the production and characterization of different EPSs produced by the recently isolated Paenibacillus sp. 2H2. A final EPS titer of 4.54 g L −1 was recovered after a 17-h fermentation, corresponding to a volumetric productivity of 0.27 g L −1  h −1 . Remarkably, supplying the fermentation with specific carbon and nitrogen sources could be exploited for the production of different polymers. A pure heteropolysaccharide composed of glucose, mannose, galactose, and glucuronic acid (3.5:2:1:0.1) was obtained when using glucose/glycerol and peptone as substrates. A pure levan-type polymer or mixture of both polymers was observed with sucrose and NaNO3 or peptone. To our knowledge, this is the first report that nutrients, particularly nitrogen sources, can be used to fine-tune EPS production in Paenibacillaceae . Rheological characterization of the heteropolysaccharide revealed impressive thickening properties, suggesting its potential application in commodity materials.